Eficiência do processo de tratamento primário de efluentes domésticos com o uso da prensa parafuso (screw press) - VALE, Grazielle Barbosa do (2018)
Accelerated urban growth is aligned with the increase in the consumption of natural resources, especially in water for human consumption, which directly results in the production of sanitary sewage in Brazil. In Brazil about 51.92% of the population has access to sanitary sewage and only 44.92% of the country's sewage is treated. The State of Pernambuco generates a volume of sewage in the order of 1.5 million m³ per day, based on its population of about 9.5 million inhabitants, of which only 20% has access to the sewage network. Another factor linked to sanitary sewage is sludge generated at Wastewater Treatment Plants, which, although corresponding to only 1-2% of the volume of treated sewage, is considered complex and demands high costs. Thus, the objective of this work is to evaluate the efficiency of a process of primary treatment of domestic effluents with the use of the screw press. In order to study the efficiency of this primary treatment process using the screw press, a domestic effluent treatment station was installed that implemented the equipment. A data survey was carried out, through photographic records and semi-structured interviews with a thematic roadmap, to identify the effluent and sludge treatment processes. In order to characterize the raw and treated effluent, monthly collections were carried out during the period from 01/2014 to 06/2018, with variations in the quality of the primary treatment during the period in which the drying beds were used for sludge dewatering and a period in which the "ETE A" already operated with the screw press. The physico-chemical collections and analyzes were carried out with reference to the methodology described in the Standard Methods for the Examination of Water and Wastewater. The efficiency of the primary treatment with the use of the screw press was obtained by means of a comparison between the results in the period that the TEE operated using drying beds (2014-2015) with the results after incorporation of the screw press to the process (2016-2018). The characterization of the sludge indicated a high degree of mineralization due to its composition having high plot of Volatile Suspended Solids. The solids content of 12% above the primary sludge characteristic range (2-7%) indicates the need for a higher frequency of removal. With the increase of efficiency in the removal of BOD the unit started to release less polluting in the receiving body reducing the environmental impacts. The average efficiency for the DBO parameter in 2014 to 2015 was 26% and with the use of the screw press and from 2016 to 2018 the result was 51%, a result higher than expected for primary processes (30%). The screw press showed to be efficient in the removal of organic load, with removal 220% greater than the drying bed process. Screw press has proven to be advantageous in terms of decreasing the time and increase of sludge processing capacity, low operator exposure to unhealthy conditions and reduced labor requirements, mitigation of the release of unpleasant odors and proliferation of insect flies.